Temperature Drives the Evolutionary Diversification of Male Harm in Drosophila melanogaster Flies. - Londoño-Nieto, C.; Butler-Margalef, M.; García-Roa, R.; Carazo, P. (Ecology Letters, 2025)
Sexual selection often leads to sexual conflict via pre-copulatory (harassment) and/or copulatory (traumatic insemination) male harm to females, impacting population growth, adaptation and evolutionary rescue. Male harm mechanisms are diverse and taxonomically widespread, but we largely ignore what ecological factors modulate their diversification. Here, we conducted experimental evolution under low- (20°C ± 4°C), moderate- (24°C ± 4°C) and high-temperature (28°C ± 4°C) regimes in Drosophila melanogaster, a species with male harm via harassment and seminal fluid proteins (SFPs), to show that temperature drives the divergent evolution of sexual conflict. At the low-temperature regime, evolution resulted in reduced and less plastic harassment (i.e., pre-copulatory harm) while at the high-temperature regime, it was characterised by responses in the seminal proteome driven by differential expression of SFPs. Our results suggest that temperature can be key to understanding the past diversification and future (global warming) evolution of sexual conflict, and the maintenance of genetic variation in male harm traits.